EMPLOYEE PARTICIPATION IN DECISION MAKING AND EMPLOYEE JOB SATISFACTION: THE MODERATING ROLE OF EMOTIONAL INTELLIGENCE (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This research study investigated the relationship  between employee participation in decision  making, emotional intelligence and employee job  satisfaction, and the extent to which emotional  intelligence moderated the relationship between  employee participation in decision making  and employee job satisfaction. The study was  conducted on 383 banking sector employees  working in J&K, India. Results posited that  employee participation in decision making and  emotional intelligence had significantly positive  influence on employee job satisfaction, with  emotional intelligence having higher impact.  Emotional intelligence also moderated the  relationship between employee participation in  decision making and employee job satisfaction.  The study implications and limitations were  discussed.
Keywords: Jammu & Kashmir; emotional intelligence; participation in decision making; employee job satisfaction